ELASTISITAS PENDAPATAN ASLI DAERAH (PAD) DI INDONESIA PADA ERA OTONOMI DAERAH - Ratna Christianingrum; Ade Nurul Aida (Pusat Kajian Anggaran, 2021)
PAD is revenue obtained by the region which is collected based on regional regulations in accordance with statutory regulations.The elasticity of PAD to GRDP is one of the indicators used to identify fiscal conditions in the regions. The elasticity describes the sensitivity of PAD to GRDP. This study will evaluate the structure of PAD by looking at the elasticity of PAD against GRDP in Indonesia, especially in the regional autonomy era. This research shows that every 1 percent of a regional economic growth, there is 1.33 percent growth of PAD. Most provinces in Indonesia have shown that the PAD obtained is elastic to regional economic growth. Thisindicates that local governments already have the ability to explore potential revenues in their regions. However, out of 34 provinces in Indonesia, there are still 5 provinces whose PAD is inelastic to regional economic growth. The five provinces are North Sumatra, Riau, Bengkulu, Central Sulawesi, and South Sulawesi. The regional governments of the five provinces need to improve their capabilities in exploring potential regional revenues.